Three-dimensional constitutive equations of polycrystalline shape memory alloy - Tokuda, M.; Ye, M.; Bundara, B.; Sittner, P. (Archives of Mechanics, 1999)
Quite unique and interesting behavior of shape memory alloy (SMA) under complex loading conditions, including the complicated path-dependence, have been observed in systematic experiments by applying some combined loads of axial force and torque to the thin-walled tubular specimen of Cu-based polycrystalline shape memory alloy. A set of constitutive equations is proposed, which can describe the complicated behavior observed in the experiments. The mesoscopic approach is employed in the formulation because the complicated behavior is closely related to the microstructural changes of the material, and the obtained equations show a reasonable agreement with the exprimental results. In the first paper, the process of modelling and the details of the formulated constitutive equations are described, and the comparison between the experimental results and the results evaluated by using the proposed constitutive equations will be shown in the second report.